Effect of repeated disinfection with madacide disinfectant solution on detail reproduction of dental stone Ramzi (Mustansiria Dental Journal, 2004)
Dental care providers are exposed to a wide variety of infections agents. This study investigated the effect of repeated applications (spaying or immersion) of disinfection on dental stone surface (reproduction ability) with medacide disinfection solution. Results demonstrated a significant reduction ni the reproduction ability with both methods of disinfection. However the spraying method had less effect than the immersion method of disinfection